Enhanced valorization of hemp stalk via chemo-catalytic and hydrothermal conversions. (1st November 2022) - Duan, Yaqi; Tao, Zhenhan; Zhu, Aiguo; Len, Christophe; Wang, Yantao; Yang, Weiran
Graphical abstract: Highlights: Enhanced valorization of hemp stalk by stepwise chemo-catalytic and hydrothermal treatment. Optimized 58 % of furfural and 40 % of 5-methylfurfural were co-yielded in chemo-catalytic process. Hydrothermal liquefaction of the lignin-rich solid residue gave a high energy recovery efficiency (88%). The solid residue was assessed to be potentially used as fuels or adsorption material. Abstract: The integration and cascade utilization of the entire lignocellulosic biomass components to obtain high value-added chemicals or fuels are of high interest. Herein, a strategy combined the chemo-catalytic and hydrothermal liquification processes was developed for the conversion of raw biomass into high value-added furanic compounds and fuels. Firstly, optimal 58% yield of furfural and 40% yield of 5-methylfurfural were co-produced from hemicellulose and cellulose components of hemp stalk powder (HSP) using formic acid and NaI as the catalysts. Then, the lignin-rich solid residue left after chemo-catalytic process, can be simply converted into bio-oil and hydrochar via hydrothermal liquefaction with a high energy recovery efficiency (88%). Elemental analysis of the bio-oils and hydrochars, as well as the adsorbing capacity of the hydrochars were also investigated and discussed. The pioneering study on simultaneously production of furfural and 5-methylfurfural, as well as the cascade valorization strategy using a green, simple and efficient way may unwrap a new direction for the entire biomass utilization.